Molecular players in neutrophil chemotaxis—focus on PI3K and small GTPases. Issue 4 (1st October 2013) - Gambardella, Laure; Vermeren, Sonja
Abstract : Review of cross‐talk between signaling intermediates during neutrophil chemotaxis, focusing on PI3K and small GTPase signaling. Abstract : Neutrophil chemotaxis is a process by which individual cells sense a gradient of chemoattractant, polarize, and then migrate toward the chemoattractant. Many features of chemotaxis are shared with other forms of cell migration. We continue to expand our understanding of the mechanisms governing these features. The rapid process through which neutrophils polarize when placed into a gradient of chemoattractant remains least well‐understood. Several key molecular players involved in the regulation of polarization have been identified. However, crosstalk among the different molecular players is required to polarize the cell and to maintain cell polarity during directional migration. The mechanism(s) by which this occurs are the subject of current investigations using experimental and computational approaches. Here, we review progress in the field, putting recent observations into context with established findings. We concentrate on the signaling processes regulated by PI3Ks, their lipid products, the role of Rho‐family small GTPases, and crosstalk between these important families of regulators.